(3TQM GdebUhQ hGdeeOhOs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s; (3jMji Hf RjGO Hf YHO Gddg Hf efXhQ GdOjdeqj, ehdi Hfj CSO (B((3Ch Hfj efbQ(B) (3CHhRcQjGA, GdeYQha HGdaQGA,J (B207 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3bGd GdabjQ Edi QMeI QHg GdeSJhgH eZaQI eMeO Hf YHO Gddg Hf eGdc GdWGFi GdLjGfi s
(3BNQgG (B:s
(3Je GdebUhQ hGdeeOhO HMeO Gddg hMSf Yhfg Ydi jO cGJHg GdabjQ GdMbjQ GdPdjd GdVYja GdQGLi Yah ehdGg cJHI dfaSg Ke def TGA Gddg HYOg s
(3GdUaMI GdChdi hGdCNjQg ZjQ hGVMJjfs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs